Changes in Nepetalactone Content and Biochemical traits of Catnip (Nepeta cataria L.) in Response to Induction of Biostimulants Compounds - N Ozhan; M Goldani; HA Naghdi Badi; A Mehrafarin; M Parsa (Institue of Medicinal Plants, ACECR, 2017)
Background: The use of organic and biological stimulants at different stages of plant growth may increase growth and yield of plants in addition to reducing environmental stresses. Objective: The aim of this study was to determine the induction effect of various formulations of chitosan, humic acid, and nicgtric acid on nepetalactone content and biochemical traits in catnip. Methods: This study, which was based on a completely randomized design (CRBD), was conducted in the research greenhouse of Medicinal Plants Research Institute, ACECR. Treatments consisted of: control, citric acid, different concentrations of humic acid, dual combinatorial formulations of chitosan and citric acid, and triple combinatorial formulations of chitosan, citric acid, and humic acid. First, the roots of the transplants were treated before being transferred to the pot. Then, about 20 days after planting, treatments were sprayed on the plants three times - once every15 days. Results: Results showed that the induction of different formulations of humic acid, citric acid, and chitosan had significant effects on plant height (P≤0.05), the number of lateral branches, the number of leaves, dry weight of leaves, stems, and shoot, content of soluble sugar, phenols, tannins, flavonoids, and nepetalactone (P≤0.01). The highest amounts - in most morpho-physiological traits - were observed 400 ppm chitosan + 800 ppm humic acid + 400 ppm citric acid treatment. The maximum content of nepetalactone was obtained at 200 ppm chitosan + 800 ppm humic acid + 400 ppm citric acid. Conclusion: The use of biostimulants formulation including humic acid, citric acid, and chitosan had a significant positive effect on improving vegetative characteristics and especially on phytochemical traits of catnip (Nepeta cataria L.).